2014
DOI: 10.1002/cam4.302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adverse events, treatment modifications, and dose intensity on survival among patients with advanced renal cell carcinoma treated with first‐line sunitinib: a medical chart review across ten centers in five European countries

Abstract: Angiogenesis inhibitors have become standard of care for advanced and/or metastatic renal cell carcinoma (RCC), but data on the impact of adverse events (AEs) and treatment modifications associated with these agents are limited. Medical records were abstracted at 10 tertiary oncology centers in Europe for 291 patients ≥18 years old treated with sunitinib as first-line treatment for advanced RCC (no prior systemic treatment for advanced disease). Logistic regression models were estimated to compare dose intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 17 publications
3
38
0
1
Order By: Relevance
“…This situation can lead to premature treatment discontinuations in cases where a pseudoprogression is detected and also biasing studies focused on biomarkers since that case will be erroneously classified, with a deleterious impact on survival [12,78].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This situation can lead to premature treatment discontinuations in cases where a pseudoprogression is detected and also biasing studies focused on biomarkers since that case will be erroneously classified, with a deleterious impact on survival [12,78].…”
Section: Discussionmentioning
confidence: 97%
“…Such a profile could, for instance, make that patients with a predicted sensitivity to one drug were preserved from unjustified dose reductions that have been correlated with a shorter survival [12].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated that on‐treatment hypertension, thrombocytopenia and relative dose intensity are useful biomarkers to predict sunitinib efficacy . Indeed, in our cohort, on‐treatment hypertension and longer sunitinib treatment period predicted better survival.…”
Section: Discussionmentioning
confidence: 51%
“…This approach can allow continuous administration and prevention of DLTs. For other VEGFR inhibitors, such as sorafenib or sunitinib, sufficient dose intensity and continuous treatment are required to maintain efficacy . Taken together, these findings show that under careful management, axitinib can exhibit feasible efficacy and tolerable safety in patients on hemodialysis.…”
mentioning
confidence: 93%